The effect of chronic stress on anti-angiogenesis of sunitinib in colorectal cancer models. (February 2015) - Liu, Jie; Deng, Guo-Hua; Zhang, Jie; Wang, Ying; Xia, Xiang-Yu; Luo, Xin-Mei; Deng, Yao-Tiao; He, Sha-Sha; Mao, Yin-Yan; Peng, Xing-Chen; Wei, Yu-Quan; Jiang, Yu
Highlights: The experiments were conducted in the context of a colorectal cancer model in mice. Psychological stress attenuated the anti-angiogenic activity of sunitinib. Norepinephrine increased the expression of VEGF and IL-8 stimulating angiogenesis. The β-adrenoceptor–cAMP–PKA signaling pathway played an important role. Beta-blockers might improve anti-angiogenic outcome under psychological stress. Abstract: Epidemiological and experimental evidence has shown that psychological stress can propel cancer progression. However, its role in anti-angiogenic therapy is not well understood. We previously found that exogenous norepinephrine attenuated the effect of sunitinib, a multi-targeted anti-angiogenic agent, in a mouse melanoma model. Here, we further evaluated the effects of chronic stress on sunitinib therapy in colorectal cancer models. We found that chronic restraint stress markedly weakened the efficacy of sunitinib, primarily through promoting the expression of vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8) to stimulate tumor angiogenesis in vivo . This effect could be sufficiently mimicked by exogenous norepinephrine and blocked by the β-antagonist propranolol. In vitro, norepinephrine up-regulated expression of VEGF and IL-8 in sunitinib-treated cancer cells mainly through the β-adrenoceptor–cAMP–PKA signaling pathway. Norepinephrine also abrogated sunitinib-induced inhibition of cancer cell migration, but had no effect on direct anti-proliferative activity of sunitinib on cancer cells. These findings suggest that psychological stress might attenuate anti-angiogenic therapy primarily through activating beta-adrenergic signaling to promote tumor angiogenesis. It is also suggested that β-blockers might improve anti-angiogenic outcome under psychological stress.